Corn productivity and topdressing application cost of nitrogen fertilizers - Weber, Wislan Cassino; Schmeling, Jeniffer Bortolini; Souza, Eduardo Lorensi; Lanzanova, Mastrangello Enivar; Silva, Danni Maisa da; Redin, Marciel (Revista de Ciências Agroveterinárias, 2023)
Nitrogen (N) is the most required nutrient in the cultivation of corn (Zea mays L.), also representing a significant share in the production costs. The objective was to evaluate the efficiency of different sources of nitrogen fertilizers applied in topdressing on the corn grain yield and their respective fertilization costs. The experiment was carried out under field conditions and without irrigation under no-tillage system, in a Red Oxissol. For sowing, 280 kg ha-1 of NPK fertilizer 12-30-20 was used for all treatments. In addition to the control treatment (NPK), four nitrogen formulations were applied in topdressing: Urea, Super N, Nitromag, and Sulfammo, applied 50% in the V3/V4 and 50% V7/V8 stages, in four replicates. Grain yield was determined at the physiological maturation. Grain yield was determined at physiological maturation. The type of nitrogen fertilizer did not influence corn grain yield, an average of 9016 kg ha-1. The largest profits were achieved with the application of Super N, Urea and Nitromag. Nitrogen fertilizers with slow and controlled N release does not promote an increase in corn grain yield in relation to Urea. The use of Super N in topdressing has the highest profitability in corn cultivation.